Site-specific N-glycosylation characterization and allergenicity analysis of globulin-1 S allele from wheat - Linglin Fu; Rongrong Wang; Jinru Zhou; Chong Wang; Yanbo Wang (Food Science and Human Wellness)
N-glycans in many proteins are of great concern because of their strong association with food allergies. Triticum aestivum (bread wheat), a major food crop, is known as one of the “Big Eight” allergenic groups. However, little research has been done about N-glycans in wheat glycoproteins. In this study, a soluble wheat glycoprotein was purified from wheat and further identified as globulin-1 S allele (GSA). The wheat GSA displayed significant IgE-binding activity. Moreover, one N-glycosylation site and 6 kinds of N-glycans were identified by mass spectrometry, including 3 high mannose types and 3 complex types. Furthermore, the IgE-binding activity of wheat GSA is proved to be reduced by the removal of N-glycan, thermal treatment (temperatures > 80 °C), and strong acidic treatment (pH 3.0). These findings would provide a better understanding of the effects of N-glycosylation, thermal treatment, and acidic treatment on the molecular characteristics of GSA, and further provide new insights into the development of hypoallergenic wheat products.